Differences in RDW Values of COVID-19 Patients with Pneumonia and Without Pneumonia at RSUM and RSUDP NTB - Indri Setiawati; Moulid Hidayat; Rina Lestari (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
Pneumonia coinfection in COVID-19 patients can be an important risk factor for patient mortality. Red blood cell distribution width (RDW) is a predictor that can determine clinical outcomes in patients with respiratory tract infections and serious illnesses, so researchers want to conduct research to determine the difference in RDW values in COVID-19 patients with and without pneumonia at RSUM and RSUDP NTB. The design of this research is cross sectional. The sampling technique used was consecutive sampling. There were 110 COVID-19 patient data used in this research. Data collection uses medical record notes. The statistical analysis used was the Mann-Whitney test. The average age of patients was 48 years ± 16 years. Most of the subjects were male (53.6%). The most common comorbidity was diabetes mellitus (21.8%). The average RDW values in COVID-19 patients with and without pneumonia were 13.9% and 13.1%. The difference in the mean RDW value in the two groups is 0.8%. This study found that clinically there were differences in the RDW values of COVID-19 patients with pneumonia and without pneumonia at RSUM and RSUDP NTB.